Anti-Stapylococcus Epidermidis of Methanolic Extracts from Some East Lombok Medicinal Plants - Dyke Gita Wirasisya; Amni Hamid; Muhamad Haikhal; Agriana Rosmalina Hidayati; Anggit Listyacahyani Sunarwidhi; Nisa Isneni Hanifa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Wounds are structural and functional disruptions of the skin that occur as a result of an injury. Wound healing is a complex tissue repair or remodelling process in response to the injury. The most common factor that causes wounds not properly heal is infection. An infection develops when microorganisms enter the body, multiply, and trigger an immune reaction in the body. This study aims to determine the activity of Jatropha multifida L., Stachytarpheta jamaicensis (L.) Vahl, Centella asiatica (L.) Urb., Euphorbia pulcherrima Willd. ex Klotzsch, and Angelica keiskei (miq.) Koidz has long been used to treat and manage wounds in East Lombok. The plants were dried and macerated with methanol; excessed solvent was evaporated. Disc diffusions were used to determine the antibacterial activity of the plant extracts. All extracts were tested against Staphylococcus epidermidis, a common cause of wound infection. Statistically, the activity of Jatropha multifida (5;10 mg/mL), Stachytarpheta jamaicensis (10 mg/mL), Centella asiatica (10 mg/mL), Euphorbia pulcherrima (M) (5, 10 mg/mL), and Angelica keiskei (2,5; 5; 10 mg/mL) extracts were comparable with positive control. However, Angelica keiskei has a wider inhibition zone than other extracts. This discovery could be served as a basis for using plants to aid wound healing, especially to combat the interference bacteria. However, further research is needed to discover the active phytochemicals involved in the antibacterial and wound healing process.